Cascaded h-bridge inverter for photovoltaic applications - Muhammad Amir Hakim Bin Zahri (Department of Electronic Engineering Technology, Faculty of Engineering Technology, University Malaysia Perlis, 2015)
This project proposed the theoretical development and implementation of a Cascaded H-Bridge (CHB) inverter for the photovoltaic (PV) application. The main objective of this project is develop CHB inverter for photovoltaic. CHB is one type of multilevel power inverter. Multilevel power inverter, new type of inverters are suitable in various high voltage and high power applications due to their ability to synthesize waveforms with better harmonic spectrum, faithful output and power quality demanding applications. There are several problem which are Photovoltaic (PV) generate the DC voltage which can be used only for DC equipment so it needs an inverter to convert the DC voltage from to AC voltage because most of the equipment appliances used AC voltage .CHB multilevel inverter is based on the series connection of single phase H-Bridge inverters with separate DC sources. This inverter circuit is simulated by using PSIM software and Proteus software and constructed on the hardware PCB board. This inverter circuit can generate 3 levels of modified square wave.CHB inverter can get the output voltage waveform will be nearly sinusoidal in AC form.